Pendampingan Pemahaman Materi Tayamum melalui Media Flip Bottle dan Puzzle di MTs Darul Ulum - Noormila, Cahya; Supriadi, Gito; Latifah, Nor (Al-DYAS, 2025)
The limited availability of adequate online media and the low utilization of creative learning tools in religious practices, particularly in teaching tayamum serve as the background of this study, given their significant impact on the effectiveness of Fikih learning in madrasahs. This study aims to analyze the effectiveness of guided instruction in enhancing students' understanding of tayamum through the use of flip bottle and puzzle media as interactive and contextual learning tools. A descriptive qualitative method was employed, involving a sample of 28 students from MTs Darul Ulum Palangka Raya, selected through purposive sampling based on their initial comprehension of the tayamum topic. Data collection techniques included observation, interviews, and documentation, while thematic analysis was used to identify patterns of improvement in understanding and student engagement. The results demonstrate that the use of flip bottle and puzzle media significantly increased students' learning interest, active participation, and conceptual understanding of the procedures and rules of tayamum. These findings support constructivist learning theory, which emphasizes active student involvement in constructing meaningful knowledge through direct experience. The main conclusion of this study is that creative media-based guidance plays a strategic role in enhancing the effectiveness of religious instruction in madrasahs. The implications include strengthening the literature on Fikih instructional media innovation and offering practical recommendations for teachers to develop interactive learning models that promote enjoyable and applicable learning experiences. This study also paves the way for future research on other ritual topics such as wudu and shalat.